Inequalities of the Bernstein type for splines of defect 2 - Babenko, V. F.; Parfinovych, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain new exact inequalities of the Bernstein type for periodic polynomial splines of order r and defect 2.